Environmental assessment guidelines for BRAC’s rural development programme - Child, Emma (BRAC Research and Evaluation Division (RED), 2020)
The study aimed to provide some guidelines for BRAC's fisheries and sericulture projects to minimise the negative environmental impacts. The methodologies described here are the simple EIA (Environmental Initial Assessment) methodologies. The guidelines provided here are organized into four different categories. These are: (A) habitat, wildlife (B) chemical use (C) natural resource use and (D)waste management. Environmental assessment guidelines are commonly conceptualized and organized according to the different environmental effects. The guidelines here have been formulated to combine this anthropocentric perspective within an ecological framework, with the intention of making the guidelines relevant to many rural development sectors. These are general guidelines for application to any rural development project, which when applied to specific sectors or types of projects will result in more specific recommendation.